Enterocolite necrosante: uma revisão da literatura - Andréa Souza Hachem; João Cesar Lyra; Érica Cristina Scarpa; Maria Regina Bentlin (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: To update the topic through a literature review. METHODS: A search was performed on the MEDLINE, PubMed, SciELO, LILACS and Cochrane platforms, using keywords on the topic and, after selecting the main articles, they were analyzed. CONCLUSION: Necrotizing enterocolitis (NEC) is an inflammation that affects the gastrointestinal tract (GIT) of newborns. The modified Bell stagind criteria classifies it, according to clinical and radiographic findings, into suspicion, confirmed or advanced. Pathogenesis is not completely understood. In term babies it occurs due to poor mesenteric perfusion. The classic form occurs in preterm infants, with multifactorial pathophysiology that includes: immaturity of the GIT, genetic predisposition, changes in the intestinal microbiota, pathogenic bacteria, characteristics of enteral nutrition and hypoxic-ischemic intestinal injury. All of these factors activate an intense inflammatory cascade, which can lead to intestinal necrosis. Risk factors are prematurity, low birth weight, sepsis, persistence of the ductus arteriosus, anemia and/or transfusion, among others. In addition to gastrointestinal symptoms (abdominal distention and pain, gastric residuals, vomiting and rectal bleeding), it has nonspecific symptoms such as temperature instability, apneas, hypoglycemia or even shock. On radiographic examination, bowel distention, pneumatosis, portal vein gas, pneumoperitoneum, intraperitoneal fluid or persistent dilated loops are found. The therapeutic approach includes fasting, broad-spectrum antibiotics, hemodynamic monitoring. Surgery is indicated when clinical worsening, perforation or suspicion of necrosis occurs. Among the preventive measures are: infection control, breastfeeding, protocols for the initiation and progression of enteral nutrition and administration of probiotics.